High temperature corrosion behaviour of austenitic stainless steel with CaCO₃ and MgCO₃ deposit - Habsah, Md Ishak
The high temperature corrosion behaviour of austenitic stainless steel was studied at 850°C, 900°C, 950°C and 1000°C for 24 to 120 hr exposure time with CaCO₃ and MgCO₃ deposit. Two commercial available austenitic stainless steel grade of AISI 304 and AISI 316L were selected. Austenitic stainless steel type AISI 304 and 316L are extensively and widely used in petrochemical, thermal power plants, boiler part, pressure vessel, etc. due to their improved corrosion resistance at elevated temperatures and corrosive conditions. The corrosion behaviour and morphological developments were investigated by weight change kinetics, morphological structures of deposits on the surface of alloy scales by scanning electron microscopy (SEM), elemental composition of oxide alloy was analyzed by energy dispersive X-Ray (EDS) analysis and the corrosion product was analyzed by X-ray diffraction. The oxidation kinetics curves of the alloy showing parabolic nature for both alloys. CaCO₃ coated AISI 304 revealed weight loss at all temperature while AISI 316L reveals weight gain at 850°C and 900°C. However at 950°C and 1000°C AISI 316L suffered weight loss through out the experiment period. Meanwhile MgCO₃ induced alloy AISI 304 suffered the weight gain at 850°C and weight loss at 900°C, 950°C and 1000°C as similar with AISI 316L. On the other hand, AISI 316L showed the highest corrosion resistance than AISI 304 because of the weight loss was relatively small than AISI 304 at 120hr. By increasing the temperature and exposure time the weight loss of alloys were increased. The developments of adherent, compact with pores and crack scale on the AISI 304 and 316L were due to evolution of CO and CO₂ gas. Fe₂O₃ , Cr₂O₃ and CaFeO₂ are corrosion products formed on the AISI 304 and 316L coating with CaCO₃. For MgCO₃ coated alloy, the corrosion product are Fe₂O₃ , Cr₂O₃ , MgFe₂O₂ and MgCrO₄ The hot corrosion morphology of the alloy induced by CaCO₃ coating shows a typical uniform attack, some pores and crack developed while on the MgCO₃ coated alloy shows some intergranular attack with crack and pores.